Cleveland Jews and the making of a Midwestern community - Martin, Sean, 1968-; Grabowski, John J. (Rutgers University Press, 2020)
This volume gathers an array of voices to tell the stories of Cleveland's twentieth century Jewish community. Strong and stable after an often turbulent century, the Jews of Cleveland had both deep ties in the region and an evolving and dynamic commitment to Jewish life. The authors present the views and actions of community leaders and everyday Jews who embodied that commitment in their religious participation, educational efforts, philanthropic endeavors, and in their simple desire to live next to each other in the city's eastern suburbs. The twentieth century saw the move of Cleveland's Jews out of the center of the city, a move that only served to increase the density of Jewish life. The essays collected here draw heavily on local archival materials and present the area's Jewish past within the context of American and American Jewish studies.